2018
DOI: 10.1002/jcb.27997
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA‐CIR regulates cell apoptosis of chondrocytes in osteoarthritis

Abstract: Background and Objectives Osteoarthritis (OA) is a complex chronic degenerative joint disease involving oxidative stress, inflammation, and apoptosis of chondrocytes. As decoys of micro RNAs, long non‐coding RNAs (lncRNAs) play important roles in various biological processes. This study was designed to investigate the interactions between lncRNA‐CIR, chondrocyte apoptosis, and the molecular mechanisms underlying OA. Methods Primary cultured chondrocytes were stressed using H2O2, IL‐1β, or TNF‐ɑ to simulate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Detailedly, the study elucidated that the amplification of lncRNA-CIR could increase the viability as well as invasion of bladder cancer cells [12]. What’s more, a recent document has pointed out that the reduction of lncRNA-CIR was able to inhibit apoptosis of chondrocytes in OA [19], and Li et al [10] have discovered that lncRNA-CIR could contribute to the degradation of chondrocyte extracellular matrix in OA. Except for cellular experiments, we have also conducted subcutaneous tumorigenesis in nude mice to observe the effect of lncRNA-CIR on osteosarcoma tumor growth in vivo, which has revealed that the suppression of lncRNA-CIR has the ability to restrain tumor growth in nude mice that had been injected with osteosarcoma cells, while the overexpressed lncRNA-CIR exerted an opposite impact.…”
Section: Discussionmentioning
confidence: 99%
“…Detailedly, the study elucidated that the amplification of lncRNA-CIR could increase the viability as well as invasion of bladder cancer cells [12]. What’s more, a recent document has pointed out that the reduction of lncRNA-CIR was able to inhibit apoptosis of chondrocytes in OA [19], and Li et al [10] have discovered that lncRNA-CIR could contribute to the degradation of chondrocyte extracellular matrix in OA. Except for cellular experiments, we have also conducted subcutaneous tumorigenesis in nude mice to observe the effect of lncRNA-CIR on osteosarcoma tumor growth in vivo, which has revealed that the suppression of lncRNA-CIR has the ability to restrain tumor growth in nude mice that had been injected with osteosarcoma cells, while the overexpressed lncRNA-CIR exerted an opposite impact.…”
Section: Discussionmentioning
confidence: 99%
“…OA is mainly a disease of the elderly, influencing principally the knees and hips [16]. Recently, a report has shown that changes in the expression levels of lncRNAs have been connected with all kinds of disease processes, including OA [17]. Furthermore, a prior study have noted that excitement of chondrocytes with Wnt-β-catenin has been conveyed to facilitate the expression levels of a variety of elements concerned with OA [18].…”
Section: Discussionmentioning
confidence: 99%
“…4-HNE and 8-oxo-dG are well-characterized oxidative damage makers that have been associated to pathological processes like mitochondrial dysfunction, apoptosis, mutagenesis, and inflammation in the joint (Abusarah et al 2017;Biniecka et al 2011a, b;Vaamonde-García et al 2017). Besides, different in vitro studies show that oxidative stress is involved in altered chondrocyte survival (Cheleschi et al 2017;Goutas et al 2018;Lu et al 2018) and act as second messengers in signaling cascades that activate the expression of catabolic mediators such as metalloproteinases like MMP-13 (Del Carlo et al 2007;Gao et al 2018), favoring cartilage degradation. We and other authors have previously described in vitro an antioxidant role of H 2 S in chondrocytes (Burguera et al 2014;Fox et al 2012).…”
Section: Discussionmentioning
confidence: 99%